Aggressive vocalizations during intergroup interactions in roost defense in the Spix's disk-winged bat - Chaves Ramírez, Silvia Elena (2023)
Animals engage in agonistic interactions to gain exclusive access to territories and resources. Understanding these interactions in bats, however, has proven difficult given their high mobility and nocturnal habits. For bats, roosts are a critical resource; thus, the study of agonistic behaviors associated with the use of these resources could provide valuable information to understand how and whether individuals monopolize them. Here, we used Thyroptera tricolor to study agonistic behaviors associated with access to a roosting resource. We experimentally studied the behavioral responses of focal groups when interacting with different intruders during the occupation of an ephemeral roosting resource. We found that T. tricolor responds more aggressively to intruders than to members of its own group, increasing the number of aggressive vocalizations. We also found differences in the rate of agonistic behaviors based on the identity of the intruders. Specifically, we observed that bats produced a large number of aggressive vocalizations when interacting with nearby intruders, supporting the “nasty neighbor” hypothesis. This study provided the first empirical evidence that aggressive vocalizations may serve as a mechanism to defend and maintain exclusive roosting sites in social groups of T. tricolor.